Campaign for Determining the Longitude of the Fundamental Point of the Astronomic Observatory in Naples — I . — The Chauvenet Problem and the Determination of Longitude by Meridian Observations - Fichera, E.; Pugliano, A. (The International Hydrographic Review, 2015)
The Astronomic Observatory in Naples has scheduled a series of observations using the most modern methods and equipment for the purpose of revising the longitude value of its fundamental point. The successive steps in this programme have been established as follows : a) Preliminary study of methods suited to modern techniques ; b) Observations and first approximation reductions ; c) Final computation and results. The author, on behalf of himself and his fellow workers, wishes to thank the Directing Committee of the International Hydrographic Bureau for having agreed to publish all the details of our research programme in the International Hydrographic Review.